Nitrogen removal from ammonium-rich pharmaceutical wastewater. A comparison between sequencing batch reactor (SBR) and sequencing batch biofilm reactor (SBBR) - Hajsardar, Mehdi; Mehdi Borghei, Seyed; Hessam Hassani, Amir; Takdastan, Afshin (Oficyna Wydawnicza Politechniki Wrocławskiej, 2018)
Biological nitrogen removal from industrial wastewater (pharmaceutical synthetic wastewater) was studied. Sequencing batch reactor (SBR) and sequencing batch biofilm reactor (SBBR) were utilized to treat ammonium-rich wastewater. No external carbon source was added to the reactors. At nitrogen loading rate (NLR) of 2.5 kg N/(m3·day), the efficiency of ammonium removal from synthetic wastewater in SBR was 86.9%. SBBR ammonium removal efficiency under fixed dissolved oxygen (DO) concentration of 0.3 mg O2/dm3 was 98.4%. Specific nitrification rate (SNR) and specific denitrification rate (SDNR) in SBR were 9.24 mg NH4 +-N/(g MLVSS·h) and 18.56 mg NO3 – -N/(g MLVSS·h), respectively. Nitrite accumulation rate (NAR) showed high correlation with DO decrement (R² = 0.983), NAR and simultaneous nitrification and denitrification (SND) had high correlation, too (R² = 0.976). SND efficiency in SBBR reached 94.1% while ammonium oxidizing bacteria (AOB) were dominant and NAR in SBBR process at the DO level of 0.3 mg O2/dm3 was 90.3%.
Environment Protection Engineering. Vol. 44, 2018, nr 3, s. 95-115
Keywords: ochrona środowiska; inżynieria środowiska; czasopisma